Pengaruh Perekonomian Indonesia di Berbagai Sektor Akibat Corona Virus Disease 2019 (Covid-19) - Ni Ketut Muliati (UNHI Press, 2020)
Pengaruh Perekonomian Indonesia di Berbagai Sektor Akibat Corona Virus Disease 2019 (Covid-19). This research was carried out based on the covid-19 outbreak that is currently happening in Indonesia and in several countries. This pandemic is not only threatening public health and safety but also threatens the economic situation in various sectors. The research method used in this research is qualitative research, data collection techniques used in this study are library research techniques. Based on the results of the Bank Indonesia (BI) Business Activity Survey (SKDU) in Quarter I-2020 indicating a decline in the economy in various sectors. This can be seen from the Weighted Net Balance (WNB) value in the first quarter of 2020 amounting to -5.56%, which is quite deep compared to 7.79% in quarter IV-2019. The decrease was caused by the decrease in demand and supply due to co-19.